Structure-activity relationship of tryptamine analogues on the heart of venus mercenaria - Greenberg, M. J. (1960)
A number of tryptamine analogues and other exciter agents have been tested on the heart of Venus mercenaria. The method of estimation of potency, especially for irreversibly acting compounds, is discussed. Specificity of action with respect to the site of action of 5-hydroxytryptamine is defined experimentally. The specific activity of tyramine and phenethylamine and the non-specific excitatory action of indole and skatole indicate that the indole ring is neither necessary nor sufficient for 5-hydroxytryptamine-like activity. Tryptamine analogues differ in mode of action as well as potency. Congeners without a 5-hydroxyl group tend to act more slowly and irreversibly as well as less strongly than 5-hydroxytryptamine. Methyl substitution also increases the time of action and difficulty of reversal. However, the potency of such compounds may be increased or decreased depending upon the position of substitution and the presence of the 5-hydroxyl group. The relations between structure and potency and mode of action are discussed. Suggestions are made concerning the effective conformation of the 5-hydroxytryptamine molecule and the nature of its receptor.